Responses in colonic microbial community and gene expression of pigs to a long-term high resistant starch diet - Sun, Yue; Zhou, LIping; Fang, Lingdong; Su, Yong; Zhu, Weiyun (Frontiers in Microbiology, 2015)
Intake of raw potato starch (RPS) has been associated with various intestinal health benefits, but knowledge of its mechanism in a long-term is limited. The aim of this study was to investigate the effects of long-term intake of RPS on microbial composition, genes expression profiles in the colon of pigs. Thirty-six Duroc × Landrace × Large White growing barrows were randomly allocated to corn starch (CS) and RPS groups with a randomized block design. Each group consisted of six replicates (pens), with three pigs per pen. Pigs in the CS group were offered a corn/soybean-based diet, while pigs in the RPS group were put on a diet in which 230 g/kg (growing period) or 280 g/kg (finishing period) purified corn starch was replaced with purified RPS during a 100-day trial. Real-time PCR assay showed that RPS significantly decreased the number of total bacteria in the colonic digesta. MiSeq sequencing of the V3-V4 region of the 16S rRNA genes showed that RPS significantly decreased the relative abundance of Clostridium, Treponema, Oscillospira, Phascolarctobacterium, RC9 gut group, and S24-7-related operational taxonomic units (OTUs), and increased the relative abundance of Turicibacter, Blautia, Ruminococcus, Coprococcus, Marvinbryantia, and Ruminococcus bromii-related OTUs in colonic digesta and mucosa. Analysis of the colonic transcriptome profiles revealed that the RPS diet changed the colonic expression profile of the host genes mainly involved in immune response pathways. RPS significantly increased proinflammartory cytokine IL-1β gene expression and suppressed genes involved in lysosome. Our findings suggest that long-term intake of high resistant starch (RS) diet may result in both positive and negative roles in gut health.